2011
DOI: 10.1124/mol.111.074195
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Action of a Broad Range of Selective κ-Opioid Receptor Antagonists Is Positively Correlated with c-Jun N-Terminal Kinase-1 Activation

Abstract: The -opioid receptor is a widely expressed G-protein-coupled receptor that has been implicated in biological responses to pain, stress, anxiety, and depression, and its potential as a therapeutic target in these syndromes is becoming increasingly apparent. However, the prototypical selective -opioid antagonists have very long durations of action that have been attributed to c-Jun N-terminal kinase (JNK) 1 activation in vivo. To test generality of this proposed noncompetitive mechanism, we used C57BL/6 wild typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(143 citation statements)
references
References 36 publications
7
136
0
Order By: Relevance
“…A number of selective KOR antagonists, including nor-BNI and JDTic, have been shown to have an exceptionally long duration of action in vivo, which might constrain their therapeutic value (see Metcalf and Coop, 2005). Receptor occupancy time-course data showed that PF-04455242 was no longer bound to KORs after 8 h, suggesting a relatively short duration of action, which has subsequently been confirmed using a warm water tail-withdrawal assay (Melief et al, 2011).…”
Section: Discussionmentioning
confidence: 78%
“…A number of selective KOR antagonists, including nor-BNI and JDTic, have been shown to have an exceptionally long duration of action in vivo, which might constrain their therapeutic value (see Metcalf and Coop, 2005). Receptor occupancy time-course data showed that PF-04455242 was no longer bound to KORs after 8 h, suggesting a relatively short duration of action, which has subsequently been confirmed using a warm water tail-withdrawal assay (Melief et al, 2011).…”
Section: Discussionmentioning
confidence: 78%
“…The mechanism of this effect is not fully understood, but may involve ligand-directed signaling (also known as biased agonism), a process by which a drug can act as an antagonist of some downstream intracellular signaling pathways while simultaneously acting as an agonist at others. The long-lasting effects of KOR antagonists in general may be related to their ability to activate c-Jun N-terminal kinase-1 (JNK), leading to a de-coupling of KORs from their intracellular signaling cascades (Melief et al, 2010;Melief et al, 2011), rather than long-term persistence of these drugs in the brain (Munro et al, 2012). From a drug development perspective, such long-lasting effects may be ultimately desirable once safety and efficacy are established, but they complicate early-phase clinical studies in humans ).…”
Section: Kor Antagonism Blocks Crf Effects On Attentionmentioning
confidence: 99%
“…Both norBNI and JDTic have antidepressant-like and anxiolyticlike properties in rodent models of stress behaviors Knoll and Carlezon, 2010), and these actions may be therapeutically useful. However, both norBNI and JDTic have very long durations of action (.3 weeks in rodents after a single dose), and this long-duration of effect is likely to be a consequence of kappa receptor inactivation through a c-Jun N-terminal kinase 1-dependent mechanism (Melief et al, 2011). Short-acting, selective kappa antagonists that do not activate c-Jun kinase have more recently been developed by scientists working at AstraZeneca (Peters et al, 2011), Pfizer , and Eli Lilly , and further development of these and related compounds is ongoing.…”
Section: Enduring Impact Of Avram Goldstein's Discovery Of Dynorphinmentioning
confidence: 99%